UPAYA PENINGKATAN HASIL BELAJAR IPS KELAS II SD NEGERI II KEMLOKO DENGAN MENGGUNAKAN MODEL MAKE A MATCH - Dwi Wulandari (Universitas Sarjanawiyata Tamansiswa, 2017)
IPS learning process that occurs at SDN II Kemloko 2nd grade class has not been achieved its satisfactory. This is due to the way the teachers teach which is still in mediocre level, in a way of providing the students with interesting learning method and interesting models that may make students happy to follow the learning activities. By the result, the students’ learning outcomes for the 2nd grade class at SDN II Kemloko still below the pre-determined score, commonly known as KKM. In order to make this condition better, the researchers are triggered to conduct a research by implementing a Class Action Research (PTK), by referring to a research model raised by Thursday and Mc. Taggart. That research model proposes 4 important stages, which are (1) preparation / planning, (2) implementation of the action, (3) observation / observation, (4) reflection. In this classroom action research, the researchers implement a learning model, which is Make a Match. Afterwards, the result shows that the 2nd grade students can experience learning outcome. It turned out that after using this model of Make a Match, there is a significant improvement. The results obtained from cycle 1 portraying a number of 17 students shows that there are 9 students who successfully accomplish the task, which is equivalent with 52.94%, and the rest of the students, which are 8 students, are not able to accomplish the task, equivalent with 47.06%. Further, the second cycle presents that the students who pass the results are 10 students with a percentage of 58.82%, while the unaccomplished ones are 7 students with a percentage of 41.18%. According to the results, the result shows that the accomplished number of students is above the average. It is strongly suggested that others may implement the learning model of Make a Match, particularly teachers.